Existence of weak-renormalized solution for a nonlinear system - Climent, B. (Revista Matemática Complutense, 2002)
We prove an existence result for a coupled system of the reactiondiffusion kind. The fact that no growth condition is assumed on some nonlinear terms motivates the search of a weak-renormalized solution.